Polonistyka rosyjska w pierwszej dekadzie XXI wieku (uwagi polskiego rusycysty) - Wołodźko-Butkiewicz, Alicja (Acta Polono-Ruthenica, 2008)
Polish Studies in Russia have considerably increased their activity since the political transformations of the 1980s and 1990s, to the extent that can be compared to Russian Studies in Poland. The lack of censorship constraints, the use of new research methodologies as well as the benefits of cooperation with numerous centres of Slavonic Studies resulted in contributing a lot of novelty to the research upon Polish literature, history and culture. This article covers the most vital achievements of Polish studies in Russia, including Polish-Russian projects, in particular the so-called imagologic research, referring to cultural relations between Poland and Russia and mutual perception of the two nations. The article presents the centres of Polish studies in Russia - the Moscow State University, the Saint-Petersburg State University, the State University for the Humanities (RGGU), the Institute for Slavonic Studies at the Russian Academy of Sciences and the Kaliningrad State University. It also enumerates the most noted academic researchers and tutors for a few generations of specialists in Polish Studies, i.e. Professor Elena Cybenko, Professor Viktor Chorev, Professor Aleksy Dimitrovski and Professor Aleksander Lipatov. The coverage also includes erudite and innovative monographies published during the last decade, concerning the history of Poland and Polish literature of different periods, ranging from 17th century to the present, for instance a monography by Natalia Filatova about Kazimierz Brodzinski, a study by Maria Leskinen concerning the phenomenon of sarmatism, by Pawel Iwinski about Mickiewicz and Pushkin, by Andrej Baranov about the influence of Fyodor Dostoyevsky's literature on the Polish literature at the turn of 19th and 20th century, by Viktoria Tichomirova about the Polish prose devoted to the Second World War and a monography by Irina Adelgejm about the contemporary Polish literature after 1989. Analogies between the present situation of Russian Studies in Poland and Polish Studies in Russia were also taken into consideration.